ANALISIS CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE YANG DIPENGARUHI OLEH GOOD CORPORATE GOVERNANCE, UKURAN PERUSAHAAN, DAN LEVERAGE - Devi Fitriyani; K Bagus Wardhianto; Mediya Destalia (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2022)
This study aims to discover the effects of Good Corporate Governance, company size, and leverage on the disclosure of Corporate Social Responsibility. The study population contains of 44 companies in the banking sector that are listed on Indonesia Stock Exchange during the 2016-2019 period and a sample of 10 companies was obtained using the purposive sampling method. The data analysis technique used in this study is the panel data regression analysis with E-views 12 program as the data analysis tool. The results show that company size partially has a positive and significant effect on the disclosure of Corporate Social Responsibility, meanwhile the Good Corporate Governance and leverage variables give positive but not significant effects on the disclosure of Corporate Social Responsibility. Simultaneously the variables of Good Corporate Governance, company size, and leverage significantly affect the disclosure of Corporate Social Responsibility.